Mobipag: integrated mobile payment, ticketing and couponing solution based on NFC - Rodrigues, Helena (2014)
The adoption of mobile payment systems is known to face multiple concerns regarding security, usability and value proposition. In this work, we start from the assumption that initial acceptance will always be weak because of the lack of an established usage frame. Instead, we focus on understanding how we can leverage upon the real contact with the technology to create a solid path for gradual acceptance through the development of new practices and the increasing perception of value. In this study, we report on our findings with a real-world prototype of a NFC-based payment system. We identify a set of design lessons that may help to improve the initial phases of NFC-based payment deployments and provide a path for the adoption that focuses on positive initial user experiences and early adoption scenarios.